Developing a diabetes prevention education programme for community health-care workers in Thailand: formative findings. - Kitti Sranacharoenpong (2018)
The aim of this study was to investigate barriers to and supports for implementing a diabetes prevention education programme for community health-care workers (CHCWs) in Chiang Mai province, Thailand. The study also aimed to get preliminary input into the design of a tailored diabetes prevention education programme for CHCWs. Thailand has faced under-nutrition and yet, paradoxically, the prevalence of diseases of over-nutrition, such as obesity and diabetes, has escalated. As access to diabetes prevention programme is limited in Thailand, especially in rural and semi-urban areas, it becomes critical to develop a health information delivery system that is relevant, cost-effective, and sustainable. Health-care professionals (n = 12) selected from health centres within one district participated in in-depth interviews. In addition, screened people at risk for diabetes participated in interviews (n = 8) and focus groups (n = 4 groups, 23 participants). Coded transcripts from audio-taped interviews or focus groups were analysed by hand and using NVivo software. Concept mapping illustrated the findings. Health-care professionals identified potential barriers to programme success as a motivation for regular participation, and lack of health policy support for programme sustainability. Health-care professionals identified opportunities to integrate health promotion and disease prevention into CHCWs' duties. Health-care professionals recommended small-group workshops, hands-on learning activities, case studies, and video presentations that bring knowledge to practice within their cultural context. CHCWs should receive a credit for continuing study. People at risk for diabetes lacked knowledge of nutrition, diabetes risk factors, and resources to access health information. They desired two-way communication with CHCWs. Formative research supports the need for an effective, sustainable programme to support knowledge translation to CHCWs and at-risk populations in the communities they serve. Ultimately, this should support chronic disease prevention in Thailand.